Determinants of macroeconomic variables effect stock market return: empirical evidence from Malaysia and Singapore / Amirah Jamiahan - JAMIAHAN, AMIRAH (Faculty of Business Management, 2017)
The study was aimed to examine the nexus between macroeconomics variables and stock market returns on Malaysia and Singapore. Variations in macroeconomics variables affect the performance of stock market. Stock market returns are not fixed as it may vary from time to time. It may be positive or negative. The macroeconomics variables consist of money supply, exchange rate and consumer price index. The study was conducted using monthly basis data from 1991 until 2016. Time-series data analysis was used to determine whether there was a statistically significant relationship between stock market returns and money supply, exchange rate and consumer price index. The data are then analyses using Econometric Views (Eviews). This study used Ordinary Least Square (OLS) method to compute the statistical result.